Dietary habits and the short-term effects of air pollution on mortality in the Chinese population in Hong Kong. Issue 3 (30th September 2010) - Ou, Chun-Quan; Wong, Chit-Ming; Ho, Sai-Yin; Schooling, Mary; Yang, Lin; Hedley, Anthony J; Lam, Tai-Hing
Abstract : Background: Both diet and air pollution are associated with mortality risks. However, no epidemiological study has examined the potential interaction between diet and air pollution on mortality. We assessed their interaction on an additive scale. Methods: We analysed the data on daily concentrations of ambient air pollutants (PM10, NO2, SO2 and O3 ) and a total of 23 484 deaths in 1998 in Hong Kong. A standardised questionnaire was used in all four death registries to collect food frequency data from proxy respondents while waiting for the registration to be completed. We fitted a linear odds ratio model and estimated excess relative risk due to the interaction (ERRI) between air pollution and regular consumption (at least once per week) of each food item to measure departure from additivity of effects on mortality. Results: We observed consistently negative ERRI between all of the four pollutants and regular consumption of vegetables, fruits and soy. The effects of PM10, NO2 and O3 were significant smaller in the subjects who regularly consumed fruits than those who never or seldom consumed such food. The effect modification of soy consumption on PM10, NO2 and SO2 associated mortality was also found statistically significant. However, regular consumption of dairy products was associated with significant increased effects of PM10 and NO2 . Conclusions: This study provides insight into dietary habit as one of the modifiers of health effects of air pollution. Our findings merit further studies to characterise the influence of diet on air pollution-related health and elucidate the underlying mechanisms.